Use of diploid species of gossypium in studies and breeding of tetraploid cotton for drought resistance - Souza, José Gomes de; Silva, Jorge Vieira da; Neto, Francisco Alves (Pesquisa Agropecuaria Brasileira, 1991)
Monosomic lines for several chromosomes added to Gossypium hirsutum from diploid wild species were tested for several physiological traits linked with drought resistance. Fourteen lines with good vigour and outstanding physiological characteristics were identified out of thirty and separated in two groups according to their high or low water potential after drought treatment. These two groups are being used in a recurrent selection program for drought resistance in order to facilitate the transfer of genes from diploid wild species to cultivated G. hirsutum.